Corrections: On the identity of Aleochara (Coprochara) pauxilla (Mulsant & Rey, 1874) (Coleoptera: Staphylinidae). - Maus, Christian (Beiträge zur Entomologie = Contributions to Entomology, 2001)
Nomenklatorische Handlungen pauxilla Mulsant & Rey, 1874 (Aleochara), syn. n. of Aleochara verna Say, 1836 [correction to 51(1): 228]